ASSESSING ACADEMIC WRITING IN HIGHER EDUCATION : COGNITIVE, MOTIVATIONAL, AND PEDAGOGICAL PERSPECTIVES - Khaoula Manaa (International Journal of Innovative Technologies in Social Science, 2025)
Despite long-standing formal instruction, the evaluation of students’ written production at university continues to reveal persistent shortcomings. This article identifies four interrelated challenges that hinder the development of academic writing: (1) students’ ambivalent relationship to French—vis-à-vis the growing prominence of English—which affects motivation; (2) pedagogical practices that privilege linguistic sub-systems and the final product over a process-oriented approach; (3) negative perceptions of drafting, often dismissed as time-consuming; and (4) the sacralization of writing as a rigid, intimidating act. Drawing on didactic and cognitive models of writing, the paper proposes concrete avenues to desacralize writing and cultivate competence: authentic communicative tasks, explicit teaching of the writing process (planning–composing–revising), and collaborative revision with formative assessment. These strategies aim to help learners progressively build both competence and confidence in academic writing.